Long-Term Outcomes of Whole Gland Salvage Cryotherapy for Locally Recurrent Prostate Cancer following Radiation Therapy: A Combined Analysis of Two Centers. Issue 3 (18th September 2021) - Chin, Joseph L.; Lavi, Arnon; Metcalfe, Michael J.; Siddiqui, Khuram; Dewar, Malcolm; Petros, Firas G.; Li, Roger; Nogueras González, Graciela M.; Wang, Xuemei; Nair, Shiva M.; Ward, John F.; Pisters, Louis
Abstract : Purpose: Radiation refractory prostate cancer (RRPCa) is common and salvage cryotherapy for RRPCa is emerging as a viable local treatment option. However, there is a paucity of long-term data. The purpose of this study is to determine long-term outcomes following salvage cryotherapy for RRPca. Materials and Methods: Patients undergoing salvage cryotherapy for biopsy-proven, localized RRPCa from 1992 through 2004 were prospectively accrued at two centers. Preoperative characteristics, perioperative morbidity and postoperative data were reviewed from our database. The primary outcomes were overall survival (OS) and disease-specific survival (DSS). The secondary outcomes were freedom from castration-resistant prostate cancer (CRPC) and freedom from androgen deprivation therapy (ADT). Results: A total of 268 patients were identified with a median followup of 10.3 years. A total of 223 complication events were recorded; of them, 168 were Clavien I–II events and 55 Clavien III events. At 10 years, 69% had freedom from ADT and 76% had freedom from CRPC. The 10-year DSS rate was 81%, and the 10-year OS rate was 77%. A pre-salvage prostate specific antigen level of >10 ng/ml was associated with an increased risk of developing CRPC and initiation of ADT but was not associated with DSS or OS. The use of neoadjuvant ADT was associated with improved OS and DSS but did not affect freedom from CRPC or adjuvant ADT. Conclusions: Salvage cryotherapy for RRPCa provides excellent long-term freedom from ADT, CRPC and DSS with acceptable morbidity. OS at 10 years was 77%. Prospective trials are required for validation.